LONG COVID AS A RHEUMATOLOGICAL CHALLENGE: POST-INFECTIOUS AUTOIMMUNITY MECHANISMS AND CLINICAL PHENOTYPES - Kowalska, Katarzyna; Kowalewska-Kurek, Aleksandra; Grygorcewicz, Hanna; Mikuła, Laura; Strycharczuk, Justyna (International Journal of Innovative Technologies in Social Science, 2026)
COVID-19 has become an important factor modulating the autoimmune response, and its rheumatological consequences include both transient musculoskeletal complaints and full-blown autoimmune diseases. Patients experience activation of innate immunity, dysregulation of T and B lymphocytes, formation of autoantibodies, and NETosis. The rheumatological complications of COVID-19 cover a wide spectrum of phenotypes, ranging from joint pain and myalgia, through reactive arthritis, myopathies, and SLE-like phenotypes, to vascular changes associated with endothelial dysfunction and resembling vasculitis. In patients with rheumatic diseases, the course of infection is more often severe, and the risk of Long COVID is significantly increased. Rare cases of de novo autoimmune diseases have also been observed after COVID-19 vaccination. Diagnosis requires an integrated immunological and clinical assessment, and understanding the molecular basis of Long COVID is key to identifying risk factors and developing personalized therapies.